Penerapan Metode Pembelajaran Group to Group Exchange dengan Media Mind Mapping untuk Meningkatkan Hasil Belajar Biologi Siswa - Arwin Arif; Ahmad Hasyim (ALVEOLI: Jurnal Pendidikan Biologi, 2021)
This research is a Classroom Action Research which aims to determine the increase in Biology Learning Outcomes through the Group to Group Exchange Learning Method with Mind Mapping Media. The subjects of this study were 20 students of class VIII SMPN 6 Lembor Selatan, West Manggarai Regency in the odd semester of the 2019/2020 school year. The implementation of this research consisted of two cycles and the data collected were analyzed using descriptive. Based on the data the results of the study showed that the Group learning method to Group Exchange using Mind Mapping media has a positive impact in improving student learning outcomes which are marked by an increase in student learning completeness in each cycle, In the first cycle the average score of activity was 38.90, increasing in the second cycle with an average score of 72.78. Mean while, the number of students who did not complete the first cycle by an average of 65% decreased in the second cycle by an average of 10%. The use of the Group To Group Exhange method with Mind Mapping media can improve student learning outcomes in class VIII students of SMPN 6 Lembor Selatan.  Keywords: Group to Group Exchange, Mind Mapping and Learning Outcomes   Penelitian ini adalah Penelitian Tindakan Kelas yang bertujuan untuk mengetahui peningkatan Hasil Belajar Biologi melalui Metode Pembelajaran Group to Group Exchange dengan Media Mind Mapping. Subjek penelitian ini sebanyak 20 orang siswa kelas VIII SMPN 6 Lembor Selatan Kabupaten Manggarai Barat pada semester ganjil tahun ajaran 2019/2020.Pelaksanaan penelitian ini terdiri atas dua siklus dan data yang terkumpul dianalisis dengan menggunakan deskriptif.Berdasarkan data hasil penelitian menunjukkan bahwa metode pembelajaran Group to Group Exchange dengan menggunakan media Mind Mapping memiliki dampak positif dalam meningkatkan hasil belajar siswa yang ditandai dengan peningkatan ketuntasan belajar siswa dalam setiap siklus. Pada siklus I skor rata-rata aktivitas 38,90 meningkat pada siklus II dengan rata-rata 72,78. Sedangkan jumlah siswa yang tidak tuntas pada siklus I dengan rata-rata 65% menurun pada siklus II dengan rata-rata 10%. Penggunaan metode Group To Group Exhange dengan media Mind Mapping dapat meningkatkan hasil belajar siswa pada siswa kelas VIII SMPN 6 Lembor Selatan. Kata Kunci:Group to Group Exchange, Mind Mapping dan Hasil Belajar